Interaction between Pasteurella multocida B: 2 and its derivatives with bovine aortic endothelial cell (BAEC) - M. Kamal, Nuriqmaliza; Saad, M. Zamri; Masarudin, Mas Jaffri; Othman, Sarah (BioMed Central, 2017)
Background: Pasteurella multocida B:2 causes bovine haemorrhagic septicaemia (HS), leading to rapid fatalities in cattle and buffaloes. An attenuated derivative of P. multocida B:2 GDH7, was previously constructed through mutation of the gdhA gene and proved to be an effective live attenuated vaccine for HS. Currently, only two potential live attenuated vaccine candidates for HS are being reported; P. multocida B:2 GDH7 and P. multocida B:2 JRMT12. This study primarily aims to investigate the potential of P. multocida B:2 GDH7 strain as a delivery vehicle for DNA vaccine for future multivalent applications. Results: An investigation on the adherence, invasion and intracellular survival of bacterial strains within the bovine aortic endothelial cell line (BAEC) were carried out. The potential vaccine strain, P. multocida B:2 GDH7, was significantly better (p ≤ 0.05) at adhering to and invading BAEC compared to its parent strain and to P. multocida B:2 JRMT12 and survived intracellularly 7 h post treatment, with a steady decline over time. A dual reporter plasmid, pSRGM, which enabled tracking of bacterial movement from the extracellular environment into the intracellular compartment of the mammalian cells, was subsequently transformed into P. multocida B:2 GDH7. Intracellular trafficking of the vaccine strain, P. multocida B:2 GDH7 was subsequently visualized by tracking the reporter proteins via confocal laser scanning microscopy (CLSM). Conclusions: The ability of P. multocida B:2 GDH7 to model bactofection represents a possibility for this vaccine strain to be used as a delivery vehicle for DNA vaccine for future multivalent protection in cattle and buffaloes.